Wealth and regional disparities in child undernutrition: insights from national demographic and health survey - Tan, Lijing; Shahid, Muhammad; Song, Jiayi; Muhammad Naveed, Hafiz; Khan, Itbar (Frontiers in Public Health, 2025)
IntroductionIn developing countries like Pakistan, the prevalence of malnutrition embodies a multifaceted development challenge, intricately linked to structural inequalities, with disproportionate burdens among socioeconomically and geographically disadvantaged populations.MethodsDrawing on the most recent Pakistan Demographic and Health Survey (2017–18), this study examines the magnitude of child undernutrition disparities across wealth quintiles and geographic regions. This study employs the Concentration Index (CI) with decomposition analysis, alongside Oaxaca-Blinder decomposition as robust.ResultsThe results of the concentration index reveal that child undernutrition in Pakistan is deeply rooted in socioeconomic disparities, with household wealth contributing the largest share (45.6%) to overall inequality. The negative values of both relative and absolute CI confirm a pronounced pro-poor concentration of malnutrition. Regional disparities also play a significant role, with Sindh, Khyber Pakhtunkhwa, Balochistan, and FATA jointly accounting for 12.9% of inequality. Notably, maternal illiteracy emerges as a critical determinant, explaining 24.1% of the observed nutritional inequity. The results of the OaxacaBlinder decomposition disclose a pronounced wealth gap in child malnutrition, with poor households experiencing a 25.5 percentage point higher likelihood of malnutrition compared to their wealthier counterparts. Approximately 65% of the explained disparity is attributed to household wealth status, maternal education, and geographic region, underscoring the structural nature of nutritional inequalities in Pakistan.ConclusionThe study concludes that child malnutrition in Pakistan is fundamentally a structural equity issue. Addressing this issue requires multisectoral policy interventions focused on economic empowerment, regional development, and girls’ education to break the intergenerational cycle of undernutrition. Moreover, Pakistan’s extreme concentration of wealth and regional marginalization create distinct disparities that standard regional models do not fully capture. The dominance of wealth and regional factors, accounting for 65% of the explained gap, highlights the need for structural solutions, such as wealth redistribution and provincial equity funds, rather than isolated health interventions.